ANALISIS KESALAHAN NUMERASI SISWA KELAS 2 SD DALAM MENYELESAIKAN SOAL AKM PADA DOMAIN BILANGAN - Pakaya, Widi Candika; Andi Marshanawiah; Nurain Karnain (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study aims to analyze the types of numeracy errors made by second-grade elementary school students in solving questions from the Minimum Competency Assessment (AKM) in the number domain. The research employed a descriptive qualitative method with data analysis based on the Newman Error Analysis (NEA) framework, which includes five categories of errors: reading, comprehension, transformation, process skills, and encoding. The research subjects were selected purposively based on indications of errors in answering numeracy questions. Instruments used included two AKM-style numeracy questions and semi-structured interviews to explore students’ understanding and thought processes. The results showed that the subject commonly made errors in comprehension, transformation, and process skills. The student struggled to understand the context of the questions, especially in identifying place value (units digit) and performing subtraction within real-life scenarios. Errors were also found in formulating appropriate final answers. These findings highlight the need for numeracy instruction that goes beyond procedural fluency to focus on contextual understanding and conceptual clarity. Teachers are encouraged to apply more interactive and diagnostic approaches in identifying and addressing students' conceptual misunderstandings from an early age.